Sustainable Data-Centric Project Curriculum for Industry-Ready Workforce - Ramasamy, Vijayalakshmi; Ramamoorthy, Suganya (Journal of Engineering Education Transformations, 2025)
The emergent technologies such as Artificial Intelligence, Deep Learning, Data Analytics, Blockchain, and Data Visualization have created an urge for the entry-level workforce to stay up to date with the industry’s analytics requirements. Since it is evident that the growth in technology and innovation rapidly changes the nature of data-centric jobs, organizations must put in a lot of effort to train their employees, especially in cloud-based sustainable work environments. Aligning academic curricula with industry requirements has been a necessity more than an option for providing sustainable solutions. Therefore, academia and companies should work together to address real-world challenges, saving a lot of money, time, and effort along with tremendous changes in the education sector. The main objective of this research paper is to explore pilot studies by designing project-based courses specific to the data science disciplines for the students by examining current research innovations in technology and industry guidance and collaboration. To achieve this objective, we introduced courses in data science by proposing a Sustainable Data-Centric Project Curriculum. Industry-academia collaboration and offering courses relevant to current technologies play an essential role in cultivating a highly skilled workforce. Offering such courses will prepare students in computing disciplines (CSE, IT, and Data Science) to acquire the data analytics foundation to create an industry-ready workforce.